Global Perspective: "Be the Bridge" Collaboration: Our journey - Meducator, The; Jani, Priyanka; Wasyleczkoaron, Andrea; Ling, Ruth; Raycroft, Erika (The Meducator, 2019)
Students in the McMaster School of Nursing, like in other Health Sciences programs, learn about evidence-based practice in a variety of hospital settings. However, best practice must also be provided at a systems level in the community, guided by the principles of primary health care. During a third-year community health course, we were placed in the South Sherman neighbourhood, a low-income, high-priority area in Hamilton. Within this community, we learned that improving health requires looking beyond the healthcare system. Therefore, we developed an intervention to address the gap between services and residents in the area. After a successful pilot project, our initiative is now becoming a full-scale partnership between McMaster students and the Hamilton community members who act as our hosts and teachers.